The effect of opportunistic behavior on trust: An experimental approach - Cristina Romero; Meike Wollni (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2015)
Linking small farmers to global markets through contract farming has become an important policy recommendation aiming to increase farmers' income and foster rural development. Nevertheless, some of the arrangements involving small farmers have been reported to loose participants or collapse over time. Trust is an informal institution that can discourage opportunism and facilitate the compliance of contracts in a setting with an expensive and weak legal system. Nevertheless, the study of trust has been addressed mostly in lab experiments, but in the agribusiness context it has been addressed only by a few authors in a rather descriptive way. We use a framed field experiment with prior signaling on a sample of 180 small broccoli farmers in the highlands of Ecuador to explore the effect of opportunistic behavior on small farmers' trust. The results reveal that this group of farmers has lower than average trust towards unknown people. Furthermore, we use a signal that mimics the payment of a loan by the B partner as treatment in the predesigned trust game. Results show that a positive signal increases trust, but a negative signal has no effect on it. Reacting slowly to external negative signs can threaten individuals who will not protect themselves towards opportunism. If farmers do not react quickly enough, they might face larger losses and will not be able to stay in business. In addition, if informal norms include weak sanctions, contract farming will be less likely and individuals will prefer the spot market were only one-time exchanges take place.
Keywords: D02; Q13; 330; small farmers; trust; experiments; signaling; delay on payment